On the Translation of Lithuanian Names with the Genitive Case and the History of the Name Sobor Square in Vilnius - Sinočkina, Birutė (Slavistica Vilnensis, 2026)
This article examines Lithuanian noun phrases with the prepositionless genitive case and the challenges of translating them into Russian. Such Lithuanian phrases often represent set names, including various types of toponyms, names of urban objects, educational institutions, media outlets, political parties, etc. The difficulty of translating them into another language is explained by the minimal context of the two-member phrase, as well as the potential for ambiguous interpretation of the prepositionless syntactic construction. The method of rendering such phrases in a foreign language largely depends on the function the name performs and the usage traditions of the target language. The specific speech material analyzed in this article names relevant to society, including neologisms. Methods of rendering them in the Russian language can vary widely – from transcribing Lithuanian names that represent addresses to replacing the genitive form with a nominative or adjective as a coordinate modifier. Particular attention is required when translating Lithuanian phrases with national specificity, whose components do not have exact equivalents in Russian.
Keywords: transcription; Russification; Cathedral Square; Sobor Square; Europe Square; Vilnius